REFLECTIVE TEACHING OF ENGLISH EDUCATION DEPARTMENT LECTURERS IN UNIVERSITAS MUHAMMADIYAH YOGYAKARTA - Ririn Kunarti (PBI 15 UMY 037, 2015)
*37 Reflective teaching is one of strategy to develop teaching and learning process. Reflective teaching is important due to the lecturers‟ need to improve their quality of teaching and learning process. In fact, reflective teaching not only gives benefits for the lecturers, but also makes the lecturers face some obstacle in conducting reflective teaching. Hence, the purpose of this study is to investigate how English Education Department lecturers reflect their own teaching. The researcher also wants to find out the lecturers‟ obstacles on conducting reflective teaching. The respondents of this research were the lecturers from English Education Department, UMY. The first results of the study showed nine findings; they were instruction for the study, material review, using authentic reading material, using the same material, using group discussion, adding technique, condition of the students and next meeting. These findings were divided into five stages of reflective teaching. The first stage was „teach‟ which contained giving instruction for the students. The second stage was „think back‟, which consisted of material review, appropriate material and using authentic reading material. The third stage was „decide‟, which included using the same material, using group discussion and adding technique. The fourth stage was „investigate‟, included condition of the students. The fifth stage was „reframe‟, which included the planning for next meeting. This research also showed that the obstacles of lecturers when doing reflective teaching were reflective teaching in formal documentation, time allocation, alternative activity and appropriate technique.